HIGH-FREQUENCY SEISMIC NOISE: RESULTS OF INVESTIGATION IN KAMCHATKA - Saltykov V.; Chebrov V.; Kugaenko Yu.; Sinitsyn V. (My University, 2006)
The investigation of seismic noise in Kamchatka is carried out for the control of the medium stress condition and search of the strong earthquakes precursors. The main directions of this research are modulation of high-frequency seismic noise (HFSN, frequency range of the first tens of Hz, amplitudes about 10−9–10−12m) by the Earth tides and temporal variations of HFSN parameters connected with the strong earthquake preparation. For reception of the statistically significant characteristics of HFSN and tides connection it was necessary to carry out long-term HFSN observations in points free from anthropogenous influence as far as possible. The station of HFSN observation was organized in the settlement Nachiky. The sensor is a narrow-band (Q=100) piezoelectric seismometer, tuned to frequency 30Hz. Signal envelope is recorded and analyzed. The continuous HFSN registration was begun in 1990 and proceeds till now. In 2000 the second station was established in the complex geophysical observatory “Karymshina”.